Sequential Kannan Type Contractions in Partial b-Metric Spaces (Contemporary Mathematics, 2024)
This paper presents the concept of the "sequential condition" in the context of fixed point results for self-maps in partial b-metric spaces. We demonstrate the existence of a unique fixed point when this condition is satisfied. Additionally, we provide illustrative examples to showcase the application and effectiveness of our findings.
Keywords: sequential Kannan type; fixed point; partial b-metrics